The Features of the Transition of Hungary’s Regional System - Rechnitzer, János (Discussion Papers, 2012)
The transition process of the Hungarian economy and society began exactly ten years ago, and every part of these systems underwent fundamental change. The country’s regional structure and the spatial economic societal movements followed the transition too, and precisely reflected the step by step altering of the socialist political-economic system and the fast development of the new system. The effects were very spectacular, on both regional and local levels. Workplaces disappeared in large numbers in crisis regions, due to the collapse of some sectors. Regions and settlements found themselves in a crisis. The former normal contacts (e.g.: commuting directions, attraction regions) got rearranged from one day to the next. The people, the households, the participants of the economy and the political-societal actors had to deal with the difficulties of the modernisation in their residential areas, local communities and regions. Therefore knowledge and experience can always be attached to a well-defined regional unit, which represents both the individuality and the legitimacy of the transition. The same applies to the reaction of the rearrangement. Since not only individuals, but even the areas acted differently, to strengthen the positive impacts or weaken the negative impacts of the transition. In this study we outline the regional characteristics of the economic and societal transition in Hungary, and the restructuring of the spatial system. We will try to sum up the characteristics of this radical and profound economic and societal transition, their impact on the factors of the spatial structure, on the participants of the regional development, on the regional resources, and on regional politics represented on government level. Our target is to acquaint the foreign readers with Hungary’s characteristics and with the profound changes, which began ten years ago and still, continues successfully today.